Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1055/s-2002-19857
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery

Abstract: During the last 10 years, minimally invasive surgery has influenced the techniques used in every specialty of surgical medicine. This development has not only led to the replacement of conventional procedures with minimally invasive ones, but has also stimulated surgeons to reevaluate conventional approaches with regard to perioperative parameters such as pain medication. However, two major drawbacks have emerged with the introduction of this new technique: firstly, the prolonged learning curve for most surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(109 citation statements)
references
References 36 publications
0
100
0
6
Order By: Relevance
“…Laparoscopic surgery has several advantages over conventional open surgery, such as faster recovery, shorter hospitalization, less pain, and less blood loss [90]. In the past two decades, the use of laparoscopy has been continuously increasing, and its indications have also expanded, from benign diseases to malignant tumors [91,92].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery has several advantages over conventional open surgery, such as faster recovery, shorter hospitalization, less pain, and less blood loss [90]. In the past two decades, the use of laparoscopy has been continuously increasing, and its indications have also expanded, from benign diseases to malignant tumors [91,92].…”
Section: Discussionmentioning
confidence: 99%
“…Многие исследования показали, что после лапароскопических вмешательств снижаются сроки госпитализации, сокраща-ется длительность временной нетрудоспособ-ности, уменьшается болевой синдром, лучше косметический эффект [6][7][8]. Тем не менее, ми-ниинвазивнная лапароскопическая хирургия имеет ряд недостатков.…”
Section: история появления роботической хирургииunclassified
“…(Fuchs, 2002) Looking specifically at hysterectomy procedures for benign indications, a Cochrane review reported improved recovery from vaginal hysterectomy compared with abdominal and laparoscopically assisted procedures. Laparoscopic procedures were found to be similarly advantageous compared with abdominal hysterectomy.…”
Section: Surgical Techniquementioning
confidence: 99%